Enhancing Critical Infrastructure Cybersecurity in Mongolia Using Israel’s Experience - Munkhchuluun, Nomin (Mongolian Journal of Strategic Studies, 2025)
The convergence of Information Technology (IT) and Operational Technology (OT) systems in critical infrastructure presents unprecedented cybersecurity challenges for developing nations. This research examines Mongolia’s evolving critical infrastructure landscape, analyzing the vulnerabilities emerging from IT/OT integration in sectors including energy, water management, transportation, heavy industries, and telecommunications. Drawing on Israel’s successful cybersecurity framework as a comparative model, this study identifies key gaps in Mongolia’s current approach and proposes actionable recommendations for enhancing national cybersecurity resilience. The findings suggest that Mongolia must develop comprehensive national strategies, invest in specialized workforce development, and establish robust public-private partnerships to secure its critical infrastructure against increasingly sophisticated cyber threats. Монгол Улсын онц чухал дэд бүтцийн кибер аюулгүй байдлыг сайжруулахад Израилийн туршлагыг ашиглах нь Хураангуй: Мэдээллийн технологи (IT) болон үйл ажиллагааны технологийн (OT) системүүдийн нэгдэл нь хөгжиж буй улсуудын онц чухал дэд бүтцэд урьд өмнө байгаагүй кибер аюулгүй байдлын сорилтуудыг бий болгож байна. Энэхүү судалгааны хүрээнд эрчим хүч, усан хангамж, тээвэр, харилцаа холбоо, хүнд хөнгөн үйлдвэрлэл зэрэг салбарын IT/OT нэгдлээс үүсэж буй эмзэг байдлыг шинжилж, Монгол Улсын онц чухал дэд бүтцийн өнөөгийн байдалд шинжилгээ хийсэн болно. Мөн Израилийн кибер аюулгүй байдлын тогтолцоог харьцуулсан загвар болгон ашиглаж, улс орны кибер сөрөн тэсвэрлэх чадавхыг сайжруулах арга хэмжээг санал болгохыг зорив. Судалгааны үр дүнгээс үзвэл Монгол Улс буй кибер аюул, заналхийллээс онц чухал дэд бүтцээ хамгаалахын тулд иж бүрэн үндэсний стратеги боловсруулах, мэргэшсэн ажиллах хүчний хөгжилд хөрөнгө оруулалт хийх, төрийн болон хувийн хэвшлийн найдвартай түншлэлийг бий болгох шаардлагатай байна. Түлхүүр үг: IT/OT нэгдэл, кибер аюулгүй байдал, SCADA, ICS